The impact of trauma‐informed suicide prevention approaches: A systematic review of evidence across the lifespan. (8th August 2022) - Procter, Nicholas; Othman, Shwikar; Jayasekara, Rasika; Procter, Alexandra; McIntyre, Heather; Ferguson, Monika
Abstract: Trauma is associated with an increased likelihood of experiencing suicidality, indicating the need for and potential value of trauma‐informed suicide prevention strategies. The aim of this study is to systematically review published literature regarding trauma‐informed approaches for suicide prevention, and the impact on suicide outcomes. Systematic searches were conducted in eight databases (Medline, Embase, PsycInfo, Emcare, Nursing, and JBI in the Ovid platform; as well as ProQuest Psychology Database and The Cochrane Library) in March 2022, with no publication date limit. Four studies met the inclusion criteria: two randomized controlled trials and two quasi‐experimental studies. Two studies reported reductions in ideation, intent, and behaviour among youth and a cultural minority group. Few studies directly reporting suicide outcomes were identified, all were quantitative, and heterogeneity prevents generalizability across population groups. Currently, there is limited evidence focusing specifically on trauma‐informed suicide prevention across the lifespan. Additional research, incorporating lived experience voices, is needed to understand the potential of this approach, as well as how mental health nurses can incorporate these approaches into their practice.